Effects of Different Drying Methods on Extractable Phenolic Compounds from Turkey Berry (Solanum torvum) Leaves - Bautista, Mikaela Vivienne M. (Animo Repository, 2021)
In the Philippines, there is an abundance of plants rich in phenolic compounds such as Solanum torvum (turkey berry), a plant with antifungal, antibacterial, anticancer, antimicrobial, and antiviral properties; however, there is not much information on the extraction of its phenolics, especially on the best drying method that will give the highest yield. Drying reduces water which allows better extraction of the said phenolics, but different drying methods expose the phenolics to possible degradation. In this study, the effect of different drying methods, namely sun-drying, freeze-drying, and microwave-drying on the extraction of total phenolics from S. torvum leaves was investigated. The dried leaves were macerated to determine the best drying method that would give the highest content of phenolic compounds from S. torvum leaves. Sun-drying, the most energy-efficient method, resulted in the highest extraction yield of 2.14 ± 0.01 mg GAE/g d.w., which was significantly different from the yields of microwave-drying and freeze-drying. Freeze-drying resulted in the lowest yield of 1.02 ± 0.01 mg GAE/g d.w., while microwave-drying yielded 1.58 ± 0.03 mg GAE/g d.w. Due to the photosensitivity of the freeze-dried samples and the high temperature of microwave-drying, phenolic compounds have degraded resulting in lesser yields. Although microwave-drying yielded less than sun-drying, it is the most efficient drying method out of the three as it is more energy-efficient than freeze-drying and less time-consuming than the others.